An appraisal of Malaysian hospital websites as a new media tool for improving healthcare information: a systematic review - Abubakar, Adamu; Mahmud, Murni; Kartiwi, Mira; Haruna, Chiroma (INSI Publications, 2015)
Background: Given that “Hospital websites”, “Healthcare”, “Healthcare systems”, and “Hospital websites as a new media tool” are general terms relating to large amounts of important data, we narrowed our focus to perform a systematic review of Malaysian hospital websites‟ presentation of healthcare issues on the basis of “Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA)” Our systematic review is applicable to hospital website evaluation, not clinical trials. Objective: The main objective of this systematic review was to uncover the findings of previous studies and views on how hospital websites stand as a media tool for healthcare systems. Results: Thorough online and offline searching were performed according to the PRISMA criteria. Search results produced 8,268 articles from 11 online databases. The numbers of articles excluded were 2,915 (35%), 3,723 (45%) and 1,511 (18%), on the basis of duplication, focus, and eligibility of not meeting the focus criteria. 119 (2%) full-text articles were assessed as meeting the criteria for how hospital websites can stand as a new media tool for healthcare systems. The results of 44 studies were synthesized. Conclusion: Although the results identify current studies on the state of hospital websites, unfortunately the number of published studies on Malaysian hospital websites as of the time of writing was limited, and do not show how Malaysian hospital websites could be used as a new media tool to enhance the healthcare system. This has shed more light on the need to further investigate how Malaysian hospital websites can empower the Malaysian community and its healthcare system.